Recombinant Antibodies with Unique Specificities Allow for Sensitive and Specific Detection of Uncarboxylated Osteocalcin in Human Circulation - Arponen Milja; Brockmann Eeva-Christine; Kiviranta Riku; Lamminmäki Urpo; Ivaska Kaisa K (SPRINGER, 2022)
Osteocalcin is a bone-specific protein which contains three glutamic acid residues (Glu) that undergo post-translational gamma-carboxylation. Uncarboxylated osteocalcin (ucOC) may participate in the regulation of glucose metabolism, thus measurement of ucOC could be useful in evaluating interactions between bone and glucose metabolism. We developed recombinant antibodies and immunoassay to specifically detect ucOC in human blood samples. ucOC-specific recombinant antibodies were selected from an antibody library by phage display. Four candidates were characterized, and one (Fab-AP13) was used to set up an immunoassay with a pre-existing MAb. Plasma ucOC levels were measured in subjects with normal fasting blood glucose (<= 6 mmol/l,N = 46) or with hyperglycemia (>= 7 mmol/l,N = 29). Further, we analyzed ucOC in age- and gender-matched patients with diagnosed type 2 diabetes (T2D,N = 49). Antibodies recognized ucOC without cross-reaction to carboxylated osteocalcin. Antibodies had unique binding sites at the carboxylation region, with Glu17 included in all epitopes. Immunoassay was set up and characterized. Immunoassay detected ucOC in serum and plasma, with on average 1.6-fold higher levels in plasma. ucOC concentrations were significantly lower in subjects with hyperglycemia (median 0.58 ng/ml,p = 0.008) or with T2D diagnosis (0.68 ng/ml,p = 0.015) than in subjects with normal blood glucose (1.01 ng/ml). ucOC negatively correlated with fasting plasma glucose in subjects without T2D (r = - 0.24,p = 0.035) but not in T2D patients (p = 0.41). Our immunoassay, based on the novel recombinant antibody, allows for specific and sensitive detection of ucOC in human circulation. Correlation between ucOC and plasma glucose suggests interactions between osteocalcin and glucose metabolism in humans.